Sexual dimorphism in the summer bill-length of the Great Tit - Gosler, A (Nederlandse Ornithologische Unie, 1987)
It has been suggested that small differences in bill length are adaptive in the Great Tit. The present study was conducted over four breeding seasons, during which bill length differed significantly between the sexes, females on average having longer bills than their partners. Since females are significantly smaller in body size than males, this suggests that bill length is indeed important. This paper seeks a reason for this dimorphism. A method is presented to demonstrate a correlation between parental bill length and prey size by the analysis of nestling faecal sacs. The difference between the parent bill lengths explained a small but significant part of chick fledging weight (and this was highly correlated with the probability of survival). Under-weight broods were significantly more likely to be reared by like-billed parents than by more different parents. A possible explanation for the relationship between chick fledging weight and parental bill difference based on a hypothesis of parent competition is proposed. Hence it is suggested that at least part of the explanation for sexual dimorphism was due to natural selection acting against the offspring of like-billed parents.